1996
DOI: 10.3109/00365529609010354
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Relationship between Disease Activity and Psychologic Distress in Patients with Inflammatory Bowel Disease

Abstract: Over time changes in DA significantly affect psychologic distress and are closely related to corresponding increases and decreases in anxiety and depression in IBD patients. Our findings therefore suggest that the assessment of psychologic distress, particularly anxiety, should be included in the clinical management of IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 30 publications
(14 reference statements)
4
89
0
2
Order By: Relevance
“…However, studies that were more adequately powered to detect differences have found that distress levels change in parallel with disease activity 11,16,60 , and those in relapse have poorer quality of life than those in remission 61,62 . The findings from this study, showing clear differences in distress between a matched community non-IBD sample and those with active IBD, add further support to the understanding that it is not having the disease per se that relates to psychological difficulties, but rather that disease activity is pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that were more adequately powered to detect differences have found that distress levels change in parallel with disease activity 11,16,60 , and those in relapse have poorer quality of life than those in remission 61,62 . The findings from this study, showing clear differences in distress between a matched community non-IBD sample and those with active IBD, add further support to the understanding that it is not having the disease per se that relates to psychological difficulties, but rather that disease activity is pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…54 Disease activity was found to be closely paralleled by anxiety and depression levels in a clinical sample of 104 CD and UC patients followed for six months, such that improved disease was mirrored by a drop in anxiety, worsening disease was accompanied by a large increase in anxiety, and ongoing disease activity had parallel stable anxiety, with a similar pattern seen for depression. 55 In a third study, Mikocka-Walus and colleagues 56 reached a different conclusion when they assessed 59 CD and UC patients at two time points, reporting similar levels of anxiety and depression at baseline and 12 months later. However, they did not consider separately those who had different disease activity patterns (e.g., those in remission who had subsequently relapsed versus those in active or inactive disease for the whole period), potentially confounding any interpretation.…”
Section: -59mentioning
confidence: 99%
“…54,55 There is evidence to suggest depression in particular can have a detrimental impact on disease course, 28,28-59 IBD treatment outcomes, 58 and overall quality of life for IBD patients. 75,76 The relationship between depression and disease course may be influenced in part by the effect of the disorder on treatment adherence, as there is significantly poorer adherence to treatment regimens by those with a comorbid psychiatric disorder.…”
Section: Managing Comorbid Anxiety and Depression In Ibdmentioning
confidence: 99%
“…During a 6-month follow-up period, one study found a strong association between change in disease activity and anxiety level and a weaker association with depressive symptoms 40 . Changes in disease activity seemed to lead to changes in anxiety and depression.…”
Section: Ibd Related Psychological and Psychiatric Problemsmentioning
confidence: 99%